Efficacy of Miticides Applied at Tassel Stage for the Control of Spider Mites in Corn, 2020 - A. Zukoff (Kansas Agricultural Experiment Station Research Reports, 2022)
Spider mite populations peaked during the week of August 19 and declined rapidly by August 26. Mite populations were made up entirely of two-spotted spider mites (Tetranychus urticae). The Portal with Exponent, Oberon, and Zeal treatments provided the best season-long control in this trial while Portal, Onager, and Mitomax II provided the most control 14 to 21 days after treatment. The lowest overall reduction in predatory mites during the season, when compared to control plots, occurred in the Portal and Onager treatments.
Keywords: spider mites; Tetranychus; predatory mites; miticide; corn